Developing a Model of Learning Management of The Semester Credit System in Magelang Military Academy - Yoga, I Gusti Agung Ketut; Rachman, Maman; Masrukhi, Masrukhi; Hardyanto, Wahyu (The Journal of Educational Development, 2016)
Military Academy has just changed its learning management from the lesson hours system to a semester credit system and is searching for a suitable model. This study is intended to analyze the existing learning management, to develop a suitable model based on the semester credit system, and to measure its applicability. This study adopts a research and development design. The data are collected from informants, events and documents by using interviews, observation and documents, and analyzed by reduction, display and drawing conclusion. The results of the study show that the learning management based on the semester credit system in Military Academy is currently implemented by using three basic patterns, by maintaining the ranks and levels of the cadets, by providing Study Plan Cards and Study Results Cards, by using effective information technology, academic supervision and academic guidelines. The applicability tests show that the developed learning management model is effectively implemented. There are some weaknesses of the developed learning management so improvement on administration and information technology should be made. It is suggested that stakeholders should make some adjustment, provide an acceleration program for the cadets with GPA of more than 3.5 and adapt the curriculum with recent development.